Research progress on estrogen receptor-positive/progesterone receptor-negative breast cancer - Zhengjia Lu; Tingrui Wang; Lu Wang; Jia Ming (Translational Oncology)
Breast cancer, which arises from the epithelial tissue of the breast, is one of the most common cancers affecting women worldwide. Its incidence and mortality rates have been increasing in both developed and developing countries. As a hormone-dependent cancer, breast cancer is classified into several molecular subtypes based on the expression of key markers: Estrogen Receptor (ER), Progesterone Receptor (PR), Human Epidermal Growth Factor Receptor 2 (HER-2), and Ki67. PR loss is associated with endocrine resistance and a poorer prognosis in breast cancer. Despite this, the underlying mechanisms of ER-positive/PR-negative (ER+PR-) breast cancer remain poorly understood. This study aims to review recent advancements in research on ER+PR- breast cancer, analyze its clinical characteristics and molecular mechanisms, and provide recommendations for more targeted therapeutic approaches.